1992
DOI: 10.1111/j.1365-2648.1992.tb02832.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐attendance at out‐patient clinics: a case study

Abstract: Non-attendance at out-patient clinics is a persistent, worldwide problem. In contrast with previous research, a qualitative approach was used in this study to examine reasons for non-attendance at out-patient clinics in one Belfast hospital, by exploring perspectives of general practitioners (GPs), hospital staff and defaulters. Findings revealed conflicts of opinion between GPs and hospital staff on appropriate management of certain medical and postnatal patients. Patients' reasons for defaulting were wide-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 14 publications
3
36
0
Order By: Relevance
“…The most promising indication of patients not replying to the invitation was an association with a longer administrative delay (the delay from the date on the referral letter to an appointment invitation being sent by the clinic). As mentioned before, non-attendance is a combination of administrative as well as patient processes (Mason, 1992), so all efforts to eliminate potential barriers to attendance should be welcomed, for example faxed or e-mailed referrals.…”
Section: Other Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…The most promising indication of patients not replying to the invitation was an association with a longer administrative delay (the delay from the date on the referral letter to an appointment invitation being sent by the clinic). As mentioned before, non-attendance is a combination of administrative as well as patient processes (Mason, 1992), so all efforts to eliminate potential barriers to attendance should be welcomed, for example faxed or e-mailed referrals.…”
Section: Other Findingsmentioning
confidence: 98%
“…The reasons for patient non-attendance are varied and contributing factors may include administrative error as well as patient variables (Mason, 1992). For example, a questionnaire study carried out with outpatients who did not attend initial or review appointments revealed that the reasons for non-attendance included forgetting or not receiving the appointment, being too ill to attend, or, conversely, feeling better and no longer in need of the appointment (Pal et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…Rates of missed appointments have been reported to be between 20% and 50% in various mental health settings (1). Previous research on missed appointments in both medical and mental health settings has provided conflicting findings, with some, but not all, researchers finding an association between missed appointments and low socioeconomic status, younger age, low level of education, a history of missed appointments, drug or alcohol abuse, poorer social functioning, having more severe psychiatric problems, and a poor relationship with the physician (2-6).…”
mentioning
confidence: 99%
“…Fewer patients needing clinic appointments means more time is available for new referrals or patients with more complicated diseases [13]. Nonattendance rates at clinic are reduced, which usually occur due to travel difficulties or a perception by patients that no condition warranting medical evaluation exists [14]. In addition, use of medical services and costs are reduced [15].…”
Section: Discussionmentioning
confidence: 99%